Factors affecting the effectiveness of the pick and roll offense at the 2017 European Men's Championship - Spiros D. Angelou; Nikos Stavropoulos; Vasiliki Manou; Christos Galazoulas (University of Novi Sad, Faculty of Sport and Physical Education, 2021)
Abstract The evolution of basketball made the game faster, leading coaches to increase the use of pick and roll cooperation in offense. The purpose of this research was to investigate the performance time of the pick and roll every five minutes, the pair of players who participated in the pick and roll and the offensive action of the ball handler after the screen, in the European Men's Championship of 2017. The sample of the research was the sixteen games of the second round of the Championship. The instrument used for the analysis of the matches was the SportScout STA Version 3.2. Analysis with ꭓ2 (Chi-square) was used. In the results analysis, a total of 714 screens were found, of which 356 were successful (49.9%) and 358 (50.1%) failed. Most pick and rolls were performed in the second five-minute span of the third period of the games (14.8%) and in the first five-minute span of the first period (14.1%). Regarding the pairs of players participating in the action, most of them had the guard as the ball handler and the center as the screener (63.4%). In about 60% of the pick and rolls the ball handler chose to finish the action himself either by driving to the basket (31.8%) or with a shot (28.6%). The results of this study provide more information and directions to basketball coaches in order for them to better organize their training and maximize the offensive performance of their teams.